Consumer Protection in Law No. 8 of 1999 and Qur'anic Review - Rizq Ikhwanul Akbar; Septiawadi Septiawadi; Abuzar Alghifari (JIA (Jurnal Ilmu Agama), 2025)
The imbalance of economic relations between business actors and consumers has resulted in suboptimal consumer protection, especially in facing the challenges of modern trade such as e-commerce. Although the Consumer Protection Law (UUPK) Number 8 of 1999 in Indonesia has provided a legal basis and regulated the basic rights of consumers, in practice consumer awareness and the application of legal protection are still not optimal. Therefore, consumer protection must be viewed holistically, not only from the aspect of positive law, but also from the perspective of the Qur'an which instills ethics and social responsibility in business. This research uses a qualitative method with an analytical literature study, which examines national legal regulations and Qur'anic verses related to business ethics and consumer protection. The results show that the principles in the UUPK are closely aligned with the teachings of the Qur'an which emphasize fairness, the prohibition of fraud, and the responsibility of businesses, as well as consumers' rights to convenience, security, and correct information. In addition, the research identified several key issues in consumer protection, such as product safety, right to clear information, digital transactions, personal data privacy, after-sales service, price transparency, protection of vulnerable consumers, right to be heard, environmental social responsibility, and accessibility of products and services. This study concludes that the integration between positive law and Islamic values can strengthen an effective and sustainable consumer protection system in Indonesia.